The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2325967119900356
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Rotator Cuff Tears: A Network Meta-analysis of 144 Diagnostic Studies

Abstract: Background: Many imaging techniques have been developed for the detection of rotator cuff tears (RCTs). Despite numerous quantitative diagnostic studies, their relative accuracy remains inconclusive.Purpose: To determine which of 3 commonly used imaging modalities is optimal for the diagnosis of RCTs.Study Design: Systematic review; Level of evidence, 4.Methods: Studies evaluating the performance of magnetic resonance imaging (MRI), magnetic resonance arthrography (MRA), and ultrasound (US) used in the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 189 publications
1
67
0
1
Order By: Relevance
“…MRI assessment has proven to be a good standard for assessing the rotator cuff tendon integrity after repair [18]. For full-thickness rotator cuff tears, MRI has higher sensitivity and superiority than other methods [19]. The most signi cant nding of our study was that there were 5 type IV cases in SR group and 3 type IV cases in SB group.…”
Section: Discussionmentioning
confidence: 60%
“…MRI assessment has proven to be a good standard for assessing the rotator cuff tendon integrity after repair [18]. For full-thickness rotator cuff tears, MRI has higher sensitivity and superiority than other methods [19]. The most signi cant nding of our study was that there were 5 type IV cases in SR group and 3 type IV cases in SB group.…”
Section: Discussionmentioning
confidence: 60%
“…A previous meta-analysis con rmed that 3-dimensional US is very effective and highly accurate to detect full-thickness RCTs, but may lack accuracy in the diagnosis of partial tears [15]. A recent network meta-analysis of diagnostic tests performed by our team reported that high-eld MRA had the highest diagnostic value, then low-eld MRA, followed by high-eld MRI, high-frequency ultrasound, low-eld MRI, and low-frequency ultrasound [16]. However, both of two meta-analyses were performed based on the full-, partial-or any tear.…”
Section: Introductionmentioning
confidence: 79%
“…It has become a popular topic whether contrast agent is used in the application of MRI to diagnosis RCTs. A network meta-analysis of 144 diagnostic studies involving 14059 patients (14212 shoulders) demonstrated that for the detection of full-thickness tears, partial-thickness tears, or any tear, MRA had the highest sensitivity, speci city, and superiority index in three common-used imaging modalities (MRA, MRI and US), which revealed that high-eld MRA had the highest diagnostic value for detecting any tear, followed by low-eld MRA, high-eld MRI, high-frequency US, low-eld MRI, and low-frequency US [16]. In addition, another meta-analysis included 14 studies involving 1216 patients with labral lesions, revealed that MRA had the highest sensitivity and speci city compared with those of MRI and CTA, which indicated that MRA was suggested for use in patients with chronic shoulder symptoms or a pathologic abnormality [32].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A systematic review by Liang et al concluded that ultrasound is highly efficient in assessing supraspinatus tears due to its high sensitivity, specificity and accuracy [12]. However, a network meta-analysis by Liu compared the diagnostic values of MRA, MRI and ultrasound which showed that high-field MRA had the highest diagnostic value [13]. The decision to proceed to MR imaging usually depends on whether the ultrasound result is equivocal or if the clinical history and exam suggest further investigation or if surgery is being considered [9].…”
Section: Discussionmentioning
confidence: 99%